2002
DOI: 10.1007/s00417-002-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for corneal allograft rejection: intermediate results of a prospective normal-risk keratoplasty study

Abstract: The incidence of episodes of corneal endothelial allograft rejection following normal-risk keratoplasty was 13.5% within the first two postoperative years. However, the frequency of irreversible immunologic graft failure (3 per thousand) was lower than reported in the literature. Patients should be regularly followed up for at least 18 months postoperatively. Patients with underlying atopic dermatitis or dry eyes should receive special ophthalmological care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 37 publications
2
39
0
5
Order By: Relevance
“…Artificial tears are prescribed on a routine basis in our Department after PKP since we found that the incidence of immunologic graft rejections in non-high-risk keratoplasties is significantly increased in dry eye syndrome [15]. However, during follow-up only 4 mostly reversible immunological graft rejections (4.5%) occurred in the present group of patients without a significant difference between FUCHS and KC [16].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial tears are prescribed on a routine basis in our Department after PKP since we found that the incidence of immunologic graft rejections in non-high-risk keratoplasties is significantly increased in dry eye syndrome [15]. However, during follow-up only 4 mostly reversible immunological graft rejections (4.5%) occurred in the present group of patients without a significant difference between FUCHS and KC [16].…”
Section: Discussionmentioning
confidence: 99%
“…In corneal transplantation, immune reactions mostly occur between 12 and 24 months following PK 40,41 and afterwards endothelial immune reactions are rarely observed. Therefore, during this time, an immunosuppressive environment in the anterior chamber is exceptionally important, which could be maintained by high levels of active TGF-b 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее известными и широко признанными факторами ри-ска отторжения роговичного аллотрансплантата яв-ляются следующие: присутствие стромальных сосу-дов в одном или более квадрантах роговицы реци-пиента, неоваскуляризация роговицы после керато-пластики, активное воспаление глаза, герпетиче-ский кератит, заболевания глазной поверхности, атопический дерматит, молодой возраст, предше-ствующая хирургия переднего отрезка, нейротро-фическая кератопатия, большой и эксцентричный трансплантат, передние синехии [6,7].…”
Section: факторы рискаunclassified